Pendekatan Preventif dan Represif terhadap Perlindungan Hak-hak Konsumen dalam Transaksi E-Commerce - Pitriani Pitriani; Zufriani; Darlius (Jurnal Hukum Lex Generalis, 2025)
This research aims to analyse the protection of consumer rights in the context of E-commerce transactions, with a focus on preventive and refressive aspects. The subject matter raised is how the protection of consumer rights can be realised in e-commerce transactions. To answer the problem, a normative juridical research approach is used with two main approaches, namely conceptual approach and statutory approach. The research findings reveal that the protection of consumer rights in E-commerce transactions can be realised through preventive approaches such as guidance, supervision, and protection by the government to consumers. In addition, a repressive approach can also be taken to resolve E-commerce transaction disputes involving international and national aspects that include non-litigation and litigation mechanisms.